Two Models of the Relationship Between Money and Sovereignty: An Interpretation Based on John R. Commons's Institutionalism. Issue 1 (2nd January 2017) - Dutraive, Véronique; Théret, Bruno
Abstract: We present a theoretical analysis of monetary sovereignty based on John R. Commons's main works. Commons wrote extensively on money and sovereignty, but he did not provide an explicit analysis of their relationship. Through the reconstruction and interpretation of his work, we propose two models of the relationship between money and sovereignty. In the first model, monetary sovereignty is owned by private banks and is potentially in competition with political sovereignty. In the second model, money can be viewed as an agent of political sovereignty, which shares some similarities with the law as an institution of sovereignty in the modern state.